The Perceptions of Student Parents towards Teacher Performances and the Implementation of Blended Learning Approach in the Learning Period of COVID-19 - Athiyah Salwa (English Education Department - Universitas Nasional Karangturi, 2022)
Online Learning is the only learning method proposed and approved by the Indonesian Government during the Covid-19 Pandemic that happens in Indonesia one year ago. However, parents find difficulties and obstacles while accompanying their child during the learning process in their homes. This research aims to show parents’ perception and evaluation toward teachers’ performance and teaching methodology. The method used in this research is descriptive qualitative to describe parents’ opinions and reveal their arguments and suggestion to the ideal teaching and learning progress in the Covid-19 Pandemic. The instruments used for data analysis are in the form of a survey by using Google Form. The data were taken at the beginning of the second semester of the 2020/2021 academic year. The results show the majority of parents prefer the blended learning method compared to only the online learning method to use in the pandemic situation.